STEM-13. CANCER STEM CELL CYTOTOXICITY ASSAY-GUIDED TREATMENT IN RECURRENT GLIOBLASTOMA AND PROGRESSIVE ANAPLASTIC GLIOMA. (11th November 2019) - Ranjan, Tulika; Howard, Candace; Yu, Alexander; Xu, Linda; Aziz, Khaled; Jho, David; Leonardo, Jodi; Hameed, Muhammad; Karlovits, Stephen; Wegner, Rodney; Fuhrer, Russell; Lirette, Seth; et al.
Abstract: BACKGROUND: The presence of chemotherapy-resistant cancer stem cells (CSC) leading to tumor recurrence is postulated to be one of the major factors in the poor response to the current standard of care treatments in progressive high-grade gliomas. Unfortunately, in spite of several new drug discoveries for other tumor types, not many advances have been reported for this disease and therefore recurrent and progressive high-grade glioma survival remains dismal. METHODS: We have used a CLIA and CAP accredited Cancer Stem Cell Cytotoxicity Assay(ChemoID) to guide most effective chemotherapy treatments from a panel of FDA approved drugs or their combinations for 12 recurrent glioblastoma (GBM) patients and 2 progressive anaplastic gliomas, all eligible to receive a stereotactic biopsy. Patients were evaluated by MRI scans and response was assessed according to RANO criteria. RESULTS: The median age of our patient cohort was 49 years (21–63), with 11 males (79%) and 3 females (21%). We observed 6 complete responses (CR) 43%, 6 partial responses (PR) 43%, and 2 progressive diseases (PD) 14%. Of note, the two PD were observed in patients that could not be treated with assay recommended therapy due to their health status. Patients treated with ChemoID assay-directed therapy had a longer median overall survival (OS) of 13.3 months (5.4-NA) compared to the historical median OS of 9.0 months (8.0–10.8 months) previously reported (1). Notably, our recurrent and progressive high-grade glioma patient cohort treated with assay-guided therapy had a 57% probability to survive at 12 months, compared to the 27% historical probability of survival at 12 months observed in previous studies (1). CONCLUSIONS: The data suggests that the ChemoID Cancer Stem Cell Cytotoxicity Assay has the potential to help guide individualized chemotherapy choices to improve recurrent and progressive high-grade glioma patient outcome. 1) Friedman, H.S. et. al. JCO 2009 27:28, 4733–4740.